PERGESERAN GARIS POLITIK HUKUM DI INDONESIA PASCA AMANDEMEN UUD 1945 - Irwansyah, Irwansyah (Hukum tata Negara/Siyasah, 2017)
Entering the era of reform and the change (amendment) UUD 1945 then there is a change of legal plural lines in the concept of national development, with the issuance legislation No. 17 year 2007 on RPJPN, the National Guidelines of State Policy (GBHN) are no longer used as previously practiced. Thus, a guide is needed that will drive various development agendas at every level in a coordinated context with each other. Keyword: Politics, Amendment, Colonialism, Reformation